Putative Clinical Implications of Unilateral Ossified Sacrospinous Ligament - Siddiqui, Abu Ubaida; Gurudiwan, Richa; Siddiqui, Abu Talha; Gupta, Paritosh; Singh, Jivtesh (Journal of Health and Allied Sciences NU, 2020)
Introduction Sacrospinous ligament (SSL) is a thin structure that extends from the ischial spine to the lateral margins of sacrum and coccyx, anterior to the Sacrotuberous ligament (STL). The internal pudendal and inferior gluteal vessels, pudendal nerve, sciatic nerve, and other branches of sacral nerve plexus pass through the greater sciatic foramen (GSF) in close proximity to the ischial spine and SSL.Objective This study aimed to report a case encountered during the routine osteology tutorial, where one of the pelvises presented with ossified SSL on the right side along with ossification of lumbosacral and the sacroiliac joints.Case Report The SSL of the right side of the pelvis was completely ossified, extending between the ischial spine and fifth piece of sacrum. The ossification had a broad-based origin from the sacrum and tapered as in proceeded to the ischial spine. It was attached to the ischial spine with a slight enlargement. Moreover, the lumbosacral and the sacroiliac joints also appeared to be ossified.Conclusion Ossification of the SSL can restrict the lesser sciatic foramen and the greater sciatic foramen, thus causing compression of neurovascular structures traversing these areas. This can be the causative factor in pudendal nerve/sciatic nerve entrapment and can be a cause for undiagnosed chronic perineal pain. Proper anatomical knowledge and radiologic studies can be utilized for accurate diagnosis and treatment of neurovascular compression syndromes and also during reconstructive procedures of the pelvic floor and treatment of uterovaginal prolapse.
Keywords: sacrospinous ligament; sacrotuberous ligament; compression; ossification; pudendal nerve